2013
DOI: 10.24105/ejbi.2013.09.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Antimicrobial Activity of Selected Three Herbal Plants Extract with Digital Image Processing Technique

Abstract: Background and Objectives: The development in the technology have witnessed that there is a revival of interest in drug discovery from medicinal plants for treatment of the most destructive diseases. Our investigation characterizes the usage of digital image processing techniques in Matlab to process and analyze the antimicrobial effects of the selected herbal plants. Methods: The first stage of our investigation involves the extraction of components with methanol from the selected three herbal plants-Solanum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…These substances are generally found in multiple parts of the herbs, including leaves, roots, shoots, blossoms, flowers and barks. Many herbs have thus become the origins of major drugs and the pharmaceutical industries have become interested in these herbs as sources of bioactive factors [44][45][46]. Results of this study plainly revealed that the M. officinalis EO antibacterial activities on the growth of clinical and commercial strains causing infections.…”
Section: Antimicrobial Activitymentioning
confidence: 89%
“…These substances are generally found in multiple parts of the herbs, including leaves, roots, shoots, blossoms, flowers and barks. Many herbs have thus become the origins of major drugs and the pharmaceutical industries have become interested in these herbs as sources of bioactive factors [44][45][46]. Results of this study plainly revealed that the M. officinalis EO antibacterial activities on the growth of clinical and commercial strains causing infections.…”
Section: Antimicrobial Activitymentioning
confidence: 89%
“…Many plant extracts owe their potency to the presence of substances such as tannins, phenolics, micro elements, essential oils, peptides, unsaturated long chain aldehydes, alkaloids and so on. These substances are usually found in various parts of the plants like roots, leaves, shoots and bark [18]. Many plants have therefore become sources of important drugs and the pharmaceutical industries have come to consider them as a source of bioactive agents that can be used in the preparation of synthetic medicine [19].…”
Section: Discussionmentioning
confidence: 99%
“…buah solanum memiliki kandungan metabolit sekunder yaitu alkaloid, saponin, tannin, flavonoid dan steroid. Menurut penelitian [5] menunjukkan bahwa (solanum nigrum L) memiliki aktivitas antibakteri meneliti bahwa ekstrak methanol dari biji Solanum nigrum L menunjukkan aktivitas antibakteri terhadap bakteri Salmonella thypi, Bacilus subtilis, Staphylococus aureus.…”
unclassified